PEMBELAJARAN BERDIFERENSIASI SEBAGAI INOVASI KURIKULUM DAN PEMBELAJARAN DI ERA SOCIETY 5.0 ABAD 21 - Taqwim, Ahsani; Pratiwi K, Ayudiah; Nabilla Azkia, Fasya; Malfiana Fitri, Rizka; Iskandar, Sofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Differentiated learning is an important strategy in responding to educational challenges in the Society 5.0 era, which integrates technology and humanistic values. Curriculum innovation requires educators to understand the individual characteristics of students, such as learning readiness, interests, and learning profiles. This approach has been proven to increase student participation, motivation, and learning outcomes. Digital technology also supports differentiation by expanding access and flexibility of learning. This study aims to examine the practice of differentiated learning as part of curriculum innovation in Indonesia. The method used is a qualitative approach with literature study techniques, through analysis of various related scientific sources. The results of the study show that the effectiveness of differentiated learning is highly dependent on collaboration between teachers, support for educational policies, and the use of appropriate technology. A sustainability strategy is needed so that this approach can be implemented consistently and responsively to the needs of the 21st century.